Avaliação da biodistribuição elementar em larvas de peixe-zebra expostas a nanopartículas de óxido de ferro - Caloni, Matheus Ramos (2021)
We report on the evaluation of iron content and biodistribution in zebrafish larvae (Danio rerio) exposed to dextran-coated superparamagnetic iron oxide nanoparticles (SPION-DX) using the micro-PIXE technique. We compare results of elemental 2D maps and Fe quantification obtained from two different sample preparation procedures: one using sagittal slices prepared by cryo-sectioning and another using entire dehydrated larvae. Independently of the preparation method used, the Fe content in the tissues of exposed animals is significantly higher (up to 140 ppm of iron) than in the controls (less than 10 ppm), but the increase is not proportional to the exposure level. In addition, 2D elemental maps show a somewhat homogeneous Fe distribution in the larvae, with some samples showing a slight enhancement in Fe content near the gut. From the PIXE data a curve correlating the exposure (nanoparticle concentration in the fish water) to the iron content in the body was obtained, which suggests a trend of saturation at high exposure doses. Such data was supported by complementary measurements using ICP-MS technique, in which the peak concentration in the intermediate dose and saturation tendency for the maximum dose was also observed.